2010
DOI: 10.1007/s11661-010-0223-5
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion and Microstructure Correlation in Molten LiCl-KCl Medium

Abstract: Pyrochemical reprocessing in molten chloride salt medium has been considered as one of the best options for the reprocessing of spent metallic fuels of future fast breeder reactors. The unit operations such as salt preparation, electrorefining, and cathode processing involve the presence of molten LiCl-KCl eutectic salt from 673 to 1373 K (400 to 1100°C). The present work discusses the corrosion behavior of electroformed nickel (EF Ni) without and with nickel-tungsten (Ni-W) coating, 316L SS, and INCONEL 625 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Our earlier studies on Type 316L (UNS S31603) stainless steel exposed to molten LiCl-KCl salt also revealed the selective outward diffusion of Cr and formation of a Cr-rich compound at the surface and spallation. [15][16] These results are in good agreement with the EDX analysis carried out on the attacked surfaces and scales. Oxygen is present in all the top layers, indicating that these layers comprise predominantly oxides.…”
Section: Cross-sectional Studies Of Corroded Samples and Scalessupporting
confidence: 76%
“…Our earlier studies on Type 316L (UNS S31603) stainless steel exposed to molten LiCl-KCl salt also revealed the selective outward diffusion of Cr and formation of a Cr-rich compound at the surface and spallation. [15][16] These results are in good agreement with the EDX analysis carried out on the attacked surfaces and scales. Oxygen is present in all the top layers, indicating that these layers comprise predominantly oxides.…”
Section: Cross-sectional Studies Of Corroded Samples and Scalessupporting
confidence: 76%
“…As the formation of the protective oxide layer on the alloy surface is challenged in molten chloride media, the structural alloys used for the construction of an electrorefiner may suffer corrosion attack during its design life (e.g., 40 years). To screen the candidate alloys, several studies have evaluated the corrosion resistance of commercial alloys in LiCl-KCl molten salt (Shankar et al, 2010;Shankar et al, 2013a;Shankar et al, 2013b;Rao et al, 2015). In general, alloys exhibit preferential dissolution or oxidation of the active element Cr, which is induced by impurities such as moisture and oxygen in the molten salt.…”
Section: Introductionmentioning
confidence: 99%
“…Another peak at 810 cm −1 could be assigned to the W-O stretching mode [13], which indicates the existence of crystalline WO 3 . The broad Raman band detected at 507 cm −1 can be correspond to the formation of NiO on the surface of the corroded specimen [14]. Thus, it was confirmed, with the aid of Raman spectroscopy, that the main corrosion products were WO 3 and NiO.…”
Section: Cosmentioning
confidence: 59%